2018
DOI: 10.1371/journal.pone.0193900
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated sequence assembly using densely labeled optical DNA barcodes: A combinatorial auction approach

Abstract: The output from whole genome sequencing is a set of contigs, i.e. short non-overlapping DNA sequences (sizes 1-100 kilobasepairs). Piecing the contigs together is an especially difficult task for previously unsequenced DNA, and may not be feasible due to factors such as the lack of sufficient coverage or larger repetitive regions which generate gaps in the final sequence. Here we propose a new method for scaffolding such contigs. The proposed method uses densely labeled optical DNA barcodes from competitive bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Complementing our analysis with long-read PacBio sequencing of key isolates demonstrated that the overlap between experimental and theoretical barcodes (15, 19) was excellent. This comparison confirmed that the location of the bla CTX-M-15 gene along the barcode of the smaller plasmid, predicted by Cas9 restriction, was correct.…”
Section: Discussionmentioning
confidence: 94%
“…Complementing our analysis with long-read PacBio sequencing of key isolates demonstrated that the overlap between experimental and theoretical barcodes (15, 19) was excellent. This comparison confirmed that the location of the bla CTX-M-15 gene along the barcode of the smaller plasmid, predicted by Cas9 restriction, was correct.…”
Section: Discussionmentioning
confidence: 94%
“…Theoretical optical DNA maps from assembled DNA sequences were created similar to Nilsson et al . [17] with updated ligand binding constants [19]. Comparisons between theoretical and experimental optical DNA maps were performed as described previously [14, 17].…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial Artificial Chromosomes (BACs) were used to optimize the experimental settings and the P -value threshold (37,39). For details about the five BACs used in the study, see Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…To compare an experimental barcode to the human genome, theoretical barcodes based on the base pair sequence of all 24 chromosomes (GRCh38.p7 dataset, retrieved from NCBI) were generated, using previously established methods (36,37). In short, the theoretical barcode is estimated based on sequence-dependent binding constants of netropsin, a sequence-independent binding constant of YOYO-1, and the point-spread function of the microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation